Landasan Konseptual Ekonomi dan Manajemen dalam Pengelolaan Sumber Daya - Maria Fifi Yanti; Muchtar Muchtar; Khairul Afdhal (Cyber Media Indonesia, 2025)
This article aims to examine the conceptual foundations of economics and management in resource management from a comprehensive perspective. In economics, resources are understood as limited factors of production that require rational choice and efficient allocation mechanisms. Meanwhile, management emphasizes the processes of planning, organizing, directing, and controlling to ensure that resources are utilized effectively in achieving organizational goals. This study employs a qualitative approach based on literature review by examining classical and contemporary theories in economics and management. The findings indicate that integrating economic and managerial perspectives provides a more comprehensive analytical framework for understanding the dynamics of resource management, both at the organizational level and within broader systems. Economic efficiency without sound managerial governance may lead to operational ineffectiveness, while management practices lacking economic rationality can result in waste and allocation distortions. Therefore, the conceptual synergy between economics and management constitutes a crucial foundation for establishing resource management systems that are sustainable, adaptive, and value-oriented. Abstrak Artikel ini bertujuan untuk mengkaji landasan konseptual ekonomi dan manajemen dalam pengelolaan sumber daya secara komprehensif. Dalam perspektif ekonomi, sumber daya dipahami sebagai faktor produksi yang bersifat terbatas sehingga menuntut adanya pilihan rasional dan mekanisme alokasi yang efisien. Sementara itu, manajemen menekankan proses perencanaan, pengorganisasian, pengarahan, dan pengendalian untuk memastikan sumber daya dimanfaatkan secara efektif dalam mencapai tujuan organisasi. Kajian ini menggunakan pendekatan kualitatif berbasis studi literatur dengan menelaah berbagai teori klasik dan kontemporer dalam ekonomi dan manajemen. Hasil kajian menunjukkan bahwa integrasi perspektif ekonomi dan manajerial menghasilkan kerangka analitis yang lebih utuh dalam memahami dinamika pengelolaan sumber daya, baik pada level organisasi maupun sistem yang lebih luas. Efisiensi ekonomi tanpa tata kelola manajerial yang baik berpotensi menimbulkan inefektivitas operasional, sementara praktik manajemen tanpa dasar rasionalitas ekonomi dapat mengarah pada pemborosan dan distorsi alokasi. Oleh karena itu, sinergi konseptual antara ekonomi dan manajemen menjadi fondasi penting dalam menciptakan sistem pengelolaan sumber daya yang berkelanjutan, adaptif, dan berorientasi pada nilai tambah.